PROTECTION OF GEOGRAPHICAL INDICATION UNDER TRADEMARK SYSTEM: TO FIT THE SQUARE INTO THE TRIANGLE? - Mas Rahmah (Mimbar Hukum - Fakultas Hukum Universitas Gadjah Mada, 2015)
This essay will analyse the main problems of protecting Geograhical Indication (GI) under trademark law. The problems includes improper definition, inclusion of craft, the treat becomes generic, the the registration conflict and its obstacles. Furthermore, this essay assumes that trademark law seems insufficient and incompatible to protect GI. Then essay advises an alternative protection under sui generis law by firstly describing legal basis for sui generis system for GI and minimum elements in sui generis law. Finally the essay conclude whether GI in Indonesia be more appropriately protected under sui generis law or not. Saat ini, perlindungan Indikasi Geografis (IG) di Indonesia diatur di bawah rezim Hukum Merek yang menimbulkan beberapa problematika yuridis. Problematika yuridis antara lain definisi IG yang tidak pas,muatan substansi IG, benturan pendaftaran IG dan Merek serta kendala lainnya. Berdasarkan kendalakendala tersebut, makalah ini mensintesakan bahwa perlindungan IG di dalam undang-undang Merek sepertinya tidak tepat sehingga perlu dikeluarkan dari undang-undang Merek. Selanjutnya makalah ini menganalisa alternatif perlindungan IG secara sui generis system sebagai pilihan yang lebih baik, dengan terlebih dahulu memaparkan landasaan hukum sui generis system dan unsur-unsur minimal yang harus ada pada sui generis system.